PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEARSIPAN DAN PERPUSTAKAAN (DISARPUS) KABUPATEN BANDUNG BARAT - , Syifa Utami N; Kurhayadi; Asep Iwa Hidayat (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of this study is to determine how much influence partial or simultaneous motivation and work discipline have on employee performance at the Archives and Library Office (Disarpus) of West Bandung Regency. In this study, researchers used quantitative methods with descriptive analysis approaches and verification analysis. The population in this study is employees at the Archives and Library Office (Disarpus) of West Bandung Regency as 154 employees. So that the method used is Slvin, so a research sample of 102 respondents was obtained. The data analysis method uses a descriptive quantitative approach and multiple linear regression analysis with SPSS tools. Data collection was obtained from respondents using questionnaires or questionnaires. The results of this study show that there is an influence of work motivation on employee performance, there is an influence of work discipline on employee performance, and there is a joint influence of motivation and work discipline on employee performance at the West Bandung Regency Archives and Library Office (Disarpus) by 66%. That is, work motivation and work discipline can explain the variation in employee performance at the Archives and Library Office (Disarpus) of West Bandung Regency by 66%.